(untitled) (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2024)
Teachers play a pivotal role in achieving the Sustainable Development Goals (SDGs), particularly SDG 4, which aims to ensure inclusive and equitable quality education and promote lifelong learning opportunities for all. Understanding teachers’ attitudes toward these goals is crucial for effective implementation and integration into educational practices. This study explores the attitudes of teachers toward sustainable goals in education and identifies factors influencing their perspectives. A mixed-methods approach was employed, combining quantitative surveys and qualitative interviews. Data were collected from 200 teachers across various primary and secondary schools in Rivers State, Nigeria, between January and June 2024. The survey included questions on teachers’ awareness, beliefs, and attitudes toward the SDGs, particularly in the context of education. Qualitative interviews provided deeper insights into the factors shaping these attitudes. Data were analyzed using SPSS version 25.0 and thematic analysis. The findings revealed that a majority of teachers (78%) have a positive attitude toward integrating sustainable goals into their teaching practices. However, only 45% reported having adequate knowledge and resources to effectively teach sustainability concepts. Key factors influencing positive attitudes included professional development opportunities, support from school administration, and personal commitment to sustainability. Barriers identified included lack of training, insufficient resources, and perceived irrelevance of sustainability topics to the existing curriculum. The study highlights the generally positive attitudes of teachers toward sustainable goals in education, but also underscores the need for enhanced training and resources. To effectively integrate sustainability into education, policymakers and educational leaders should focus on providing comprehensive professional development, adequate resources, and supportive school environments. Addressing these needs will empower teachers to become effective change agents in promoting sustainability through education.